Muslim Community Perceptions of Sharia Boundaries in Interactions with Siblings-in-Law in Pahandut District - Najwa, Nur; Syarifuddin, Syarifuddin; Maimunah, Maimunah (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
Interaction with siblings-in-law occupies a sensitive position in Muslim family life, particularly in extended-family households where daily proximity is common. Although Islamic law clearly categorizes siblings-in-law as non-mahram, social practice often treats them as close family members, resulting in interaction patterns that blur sharia boundaries. This study examines how Muslim communities in Pahandut District understand and practice boundaries of interaction with siblings-in-law, and the factors that shape these practices. Using a qualitative field-based approach, data were collected through in-depth interviews with community members and a local religious figure, supported by document analysis. The findings show that community understanding of interaction boundaries varies significantly, influenced by kinship traditions, living arrangements, and uneven levels of religious literacy. Many informants acknowledge religious obligations in general terms but encounter practical difficulties in applying specific fiqh rules related to aurat observance, seclusion, and everyday interaction within shared domestic spaces. Analysis based on the principle of sadd al-dharā’iʿ indicates that preventive legal reasoning is weakly internalized in daily family practices. Interaction patterns that are socially normalized are often maintained despite their potential to open the way to fitnah, not due to conscious rejection of Islamic norms but because of cultural familiarity and structural constraints. These findings highlight the need for more contextual forms of religious education that address family interaction explicitly, and contribute to discussions on social fiqh by linking Islamic legal principles with lived community realities.